The Foreign Cultural Aspects Embedded in the English Textbooks of the Basic Stage in Jordan - Jafar, Fatima (Jordan Journal of Educational Sciences, 2006)
This study aimed at investigating the foreign cultural aspects compared to the Arabic aspects in English teaching textbooks for the basic stage in Jordan. The study followed textbooks content analysis for cultural aspects at the level of word and picture for names, pets, women, celebrations and social events, addressing people, and social concepts and values. The data analysis of Action Pack series, accredited for grades 1-6 at public schools showed that the ratio of foreign aspects was 76% compared to the Arabic aspects 24%, which meant that the basic stage pupil is intensively exposed to the foreign culture that might cause cultural shock, lessening the motivation to learn English because of cultural distance. The researcher recommended re-evaluating the cultural content of these textbooks, to creating a balance between the Arabic/Islamic culture and the foreign culture, enabling pupils to relate English language to real life, and preventing adopting the foreign culture at the expense of the Arabic culture.